2017
DOI: 10.1177/0146621617730392
|View full text |Cite
|
Sign up to set email alerts
|

The Information Product Methods: A Unified Approach to Dual-Purpose Computerized Adaptive Testing

Abstract: This article gives a brief summary of major approaches in dual-purpose computerized adaptive testing (CAT) in which the test is tailored interactively to both an examinee's overall ability level, , and attribute mastery level, . It also proposes an information product approach whose connections to the current methods are revealed. An updated comprehensive empirical study demonstrated that the information product approach not only can offer a unified framework to connect all other approaches but also can mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…Similar results have been observed by Kang et al (2017) within the framework of dual-objective CD-CAT (Kang et al, 2017;McGlohen & Chang, 2008;Wang et al, 2014;Zheng et al, 2018). For simultaneously estimating examinees' α i and general ability θ i , the dual-objective CD-CAT is based on a CDM and an item response theory model.…”
Section: Jsd Indexsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results have been observed by Kang et al (2017) within the framework of dual-objective CD-CAT (Kang et al, 2017;McGlohen & Chang, 2008;Wang et al, 2014;Zheng et al, 2018). For simultaneously estimating examinees' α i and general ability θ i , the dual-objective CD-CAT is based on a CDM and an item response theory model.…”
Section: Jsd Indexsupporting
confidence: 71%
“…Tatsuoka & Ferguson, 2003;Xu et al, 2003), the likelihood-or posterior-weighted KL (LWKL or PWKL) index and the hybrid KL index (Cheng, 2009), the restrictive progressive or threshold PWKL index (Wang et al, 2011), the aggregate ranked information index and the aggregate standardized information index (Wang et al, 2014), the modified PWKL (MPWKL) index (Kaplan et al, 2015), the KL expected discrimination index (W. Y. Wang et al, 2015), the posterior-weighted cognitive diagnostic model (CDM) discrimination index and the posteriorweighted attribute-level CDM discrimination index (Zheng & Chang, 2016), and the information product index (Zheng et al, 2018). The second is based on the Shannon entropy, called the Shannon entropy (SHE) procedure (Cheng, 2009;McGlohen & Chang, 2008;C.…”
mentioning
confidence: 99%
“…Dai et al (2016) have tried several values of ω (0.1, 0.3, 0.5, 0.7, and 0.9) and found that ω = 0.5 provided the best synthetic results. Besides, the information product approach with a weight of 0.5 can be considered as a natural extension of the weighted item selection (Zheng et al, 2018). Setting the weight to 0.5 is also consistent with the view that both α and θ should be considered equally.…”
Section: Discussionmentioning
confidence: 99%
“…As well as data-driven model selection, for instance, use Akaike's information criterion and Bayesian information criterion to select the CDMs. Third, the application of the new method to the dual-objective CD-CAT (McGlohen and Chang, 2008 ; Wang et al, 2012 , 2014 ; Dai et al, 2016 ; Kang et al, 2017 ; Zheng et al, 2018 ) could be investigated in the future. The dual-objective CD-CAT combines the IRT model and CDMs; therefore, it may be able to provide both an overall score and specific diagnostic information for individuals.…”
Section: Discussionmentioning
confidence: 99%